Appearance comparisons styles and eating disordered symptoms in women. (December 2016) - Lin, Linda; Soby, Meghann
Abstract: The purpose of this study was to examine the relationship between styles of upward and downward appearance comparisons and eating disordered symptoms in women. Data on upward and downward appearance comparisons, body dissatisfaction, drive for thinness, dietary restraint, and negative body talk were collected from 321 female college students. Results indicated that upward appearance comparisons were linked to higher levels of drive for thinness, body dissatisfaction, dietary restraint, and negative body talk, whereas downward appearance comparisons were linked to higher levels of drive for thinness and dietary restraint, but showed no relationship to body dissatisfaction and negative body talk. There was an interaction effect between upward and downward comparisons and body image variables. Taken together, this study suggests that downward appearance comparison does not buffer the negative effects of upward appearance comparison, and in some cases can increase negative body image outcomes. Highlights: Upward appearance comparisons were related negative body image outcomes. Downward comparisons were related to some negative outcomes, but not others. Downward comparison moderated the effects of upward comparison on body image. Downward did not buffer the negative effects of upward appearance comparison.